Probing the use of long lived intra-ligand π-π * excited states for photocatalytic systems: a study of the photophysics and photochemistry of [ReCl(CO)3(dppz-(CH3)2)] - Summers, Peter A.; Calladine, James A.; Ibrahim, Nasiru; Kusumo, Kennedy P.; Clark, Charlotte A.; Sun, Xue-Z.; Hamilton, Michelle L.; Towrie, Michael; McMaster, Jonathan; Schröder, Martin; George, Michael W. (Elsevier, 2017)
We report the excited state photophysics and photochemistry of [ReCl(CO)3(dppz-(CH3)2)] (dppz-(CH3)2 = 11,12-dimethyl-dipyrido[3,2-a:2’,3’-c]phenazine) in CH3CN using timeresolved infrared (TRIR) and Fourier transform infrared (FTIR) spectroscopy. Excitation of the 1MLCT (metal-to-ligand charge transfer) band of [ReCl(CO)3(dppz-(CH3)2)] populates a 3MLCT excited state which rapidly interconverts on a timescale < 1 ns to a long lived IL (intra-ligand) π-π* excited state with a lifetime of 190 (± 5) ns. In the presence of an electron donor (NEt3), the IL excited state of [ReCl(CO)3(dppz-(CH3)2)] can be reductively quenched to [ReCl(CO)3(dppz-(CH3)2)]− with the radical in the latter localised on the distal phenazine (phz) portion of the dppz ligand. The phz based electron in [ReCl(CO)3(dppz-(CH3)2)]− has minimal interaction with the rhenium metal centre which increases the stability of the photosensitiser in its reduced form. In non-dried, non-degassed CH3CN (1 M NEt3), [ReCl(CO)3(dppz-(CH3)2)]− shows no significant change in the carbonyl region of the IR spectrum for at least 2 hours during continuous photolysis. In addition, we investigate the use of [ReCl(CO)3(dppz-(CH3)2)]− to reduce the previously studied catalyst [NiFe2], with facile electron transfer from [ReCl(CO)3(dppz-(CH3)2)]− to form [NiFe2]–.